Mekanisme Respon Arus Bocor Isolator Luar Ruangan Di Bawah Pengaruh Iklim Tropis - Tambi Tambi; Wa Ode Zulkaida; Muh. Nadzirin Anshari Nur; Fachrur Razy Rahman (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
It is important to know the leakage current response mechanism in outdoor insulators when it rains after the dry season to predict the risk of flashover exposed to environmental pollution in aging insulators, so that it can be used as initial information by network maintenance operators to take action in the field. The main objective of this paper is to determine the effect of accumulated pollution and wetting on insulator surfaces on leakage currents at the beginning of the rainy season after the dry season based on real-time monitoring. Monitoring is carried out on polymer silicone rubber-SIR insulators and porcelain insulators installed on transmission towers or on distribution channels on days with drizzling rain and without rain on aging insulators. Based on the leakage current curve and statistical analysis results, drizzling rain during the day and night does not significantly affect the increase in leakage current in the polymer insulator, except when the temperature is above 35 â„ƒ, where the leakage current varies slightly over a wide range.